Influence of high-charge and low-charge PCE-based superplasticizers on Portland cement pastes containing particle-size designed recycled mineral admixtures. (November 2020) - Franco de Carvalho, José Maria; Schmidt, Wolfram; Kühne, Hans-Carsten; Peixoto, Ricardo André Fiorotti
Abstract: Design: and use of engineered recycled mineral admixtures obtained from industrial and mineral waste are promising strategies to increase the range of materials suitable for use in cement-based composites. In this work, Portland cement-blended pastes containing mineral admixtures designed for improving particle packing were evaluated in the presence of low- and high-charge polycarboxylate-based superplasticizers. The powders were obtained from basic oxygen furnace slag, iron ore tailings, quartz mining tailings, and quartzite mining tailings. The zeta-potentials of the particles were obtained via electrophoretic mobility. The flow properties were evaluated by rheological tests performed in a Couette type rheometer. The hydration kinetics was evaluated by isothermal calorimetry and an adapted method based on the Vicat needle test. The high-charge PCE and the finer mineral admixtures produced more stable blends. Coarser mineral admixtures led to increased flowability and delayed hydration compared to finer ones. Steel slag powders presented the most significant plasticizer effects, but also the largest setting delays and segregation tendency. Quartz-rich superfines reduced the setting delays caused by the superplasticizers. In summary, both superplasticizers were effective in improving flow properties, but the high-charge PCE was effective in preventing segregation in pastes containing mineral admixtures coarser and heavier than cement. Highlights: Rheological behavior similar-to-meliorated compared to cement-only pastes. Good interaction with different PCE-based superplasticizers. Fine powders provided lower delays in setting times and more stable mixtures. High charge PCE caused the greatest delays but provided more stable mixtures.